Characterization of proopiomelanocortin mRNA detected by in situ hybridization - Kelsey, JE (J Neurosci, 1986)
In situ hybridization is a method for detecting specific nucleotide sequences by using a labeled complementary nucleic acid probe. We have characterized in situ hybridization in rat pituitary using a cDNA probe directed against a portion of proopiomelanocortin (POMC) mRNA to show its specificity in tissue sections. This characterization includes the size of the target mRNA from tissue processed for in situ hybridization, the dissociation pattern of the cDNA:mRNA hybrid, and quantitation of changes in POMC mRNA levels in the rat pituitary intermediate lobe detected both by in situ hybridization and “dot blot” techniques.